A Review of Literature on Information Management utilizing ICT in Higher Education - Vikram Sharma (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The paper plans to study the job of Information Management (IM) utilizing Information and Communication Technology (ICT) in advanced education by leading writing survey and arrangement of articles from 2000 to 2012 so as to investigate how IM advances and applications have been created right now. The development of Information and Communication Technologies (ICT) in the most recent decade has opened new roads in Information Management that could assume significant jobs in meeting the overall provokes identified with sharing, trading and scattering information and advances in the advanced education. This paper gives an elevated level diagram of IM utilizing Information and Communication Technology (ICT) in advanced education. A basic examination is finished by considering endeavors made by experts to actualize IM utilizing ICT in advanced education.